A systemic review of vertical transmission possibility in pregnant women with coronavirus disease 2019-positive status - AlQahtani, Moath A. (J Family Med Prim Care, 2020)
An unknown pneumonia outbreak has been reported by hospitals in Wuhan, China, in late December 2019. A public health emergency of international concern announced by the World Health Organization (WHO) on the January 31, 2020. The virus named by the WHO as coronavirus disease 2019 (COVID-19). The cases reached (266,073 cases) and deaths (11,184 deaths) globally by the end of March 21, 2020, and considered as a pandemic. By a systemic review, articles and case reports revealed 74 pregnant women for the possibility of vertical transmission of the virus from COVID-19-infected mother to infant. Review also showed that there is no difference between pregnant and nonpregnant regarding clinical manifestations. Concerning the vertical transmission, none of the positive mothers had a positive infant with COVID-19 except 1 case report that showed the infant had positive COVID-19 by the throat swab, yet negative cord blood, placenta, and mother's breast milk.